2023
DOI: 10.3390/su15043823
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Architecture Fostering Green Mindfulness

Abstract: Green mindfulness seems to play an important role in promoting sustainability in architecture, but discrete areas of knowledge are still widely unknown. This study aimed to explore the publications that exist on the nexus between green mindfulness and architecture, and to find the architectural features that tend to foster green mindfulness. The study conducted a systematic literature review by searching publications from databases including Scopus, Google Scholar, and Thai Journals Online in September 2022. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Some scholars stated that architectural atmosphere consists of mass and volume, light, color, sound, and landscape [90,91], while others pointed out that materials and objects are also part of the atmosphere [50,92,93]. However, there are discrete areas of knowledge between the architectural atmosphere and mindfulness that are still widely unknown [10,18,50].…”
Section: The Architectural Atmosphere That May Influence Mindfulnessmentioning
confidence: 99%
See 3 more Smart Citations
“…Some scholars stated that architectural atmosphere consists of mass and volume, light, color, sound, and landscape [90,91], while others pointed out that materials and objects are also part of the atmosphere [50,92,93]. However, there are discrete areas of knowledge between the architectural atmosphere and mindfulness that are still widely unknown [10,18,50].…”
Section: The Architectural Atmosphere That May Influence Mindfulnessmentioning
confidence: 99%
“…By reviewing a systematic literature review [18], three mindfulness-fostering architectural concepts were identified. The first idea comes from Kawai Y's (2018) interview in Japan Society Talk, which mentioned Japanese traditional architecture.…”
Section: The Architectural Atmosphere Design Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…As people and planet, we are facing severe problems that impact our quality of life and morbidity, particularly in towns and cities. These include, among others, air pollution, natural disasters, and overheating [1][2][3][4][5][6][7][8][9][10]. While it is obvious that landscape remains a crucial element impacting quality of life, currently, we are experiencing a period of profound transformations with regards to the landscape.…”
Section: Introductionmentioning
confidence: 99%